Macli-ing Dulag: Kalinga Chief Defender of the Cordillera - Roldan, Suzanna R. (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Book review of  Doyo, Ma. Ceres P. 2015. Macli-ing Dulag: Kalinga Chief Defender of the Cordillera. Quezon City: University of the Philippines Press. 92 pp.